Principles of Organization and Functioning of Mini-CHP Plants Using Local Fuels in Conditions of Hydrogen Energy - R. S. Ignatovich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
This article discusses the principles of organization and operation of mini-CHP plants on local fuels (LF) to the conditions of hydrogen and carbon-free energy. The analysis of literary sources on the current state of development of mini-CHP plants on LF in the structure of the country's energy balance revealed a number of issues related to their operation and construction that arose after the commissioning of the Belarusian NPP. It is noted that a potential way to develop such energy sources is to switch to multi-purpose product development based on the principles of operation of the energy hub, which will potentially reduce the dependence of the energy source on the operation of the Unified Energy System (UES). The analysis of open literature sources on the potential role of LF in the transition to carbon-free energy was carried out. In this context, the operation of a mini-CHP plant on LF is considered according to two scenarios, viz. recovery of CO2 from combustion products, followed by purification to food grade and sale to direct consumers, as well as changing the operating modes of the energy source by means of the accumulation of excess electrical energy in the form of hydrogen during the operation of a mini-CHP plant in accordance with the thermal load of consumers. Based on archival data from an operating wood chip-fueled mini-CHP with an ORC module that was selected for research as an analog object, an assessment of the economic conditions for the development of mini-CHP plants on LF was made when integrating food-grade CO2 extraction units or for the production and accumulation of hydrogen into their schemes. For food grade carbon dioxide production systems, a functional dependency has been built that allows for a preliminary estimate of the value of the simple payback period when integrated into the scheme. Under the accepted conditions for the study object, the simple payback period obtained using the built dependency was less than 3 years. For systems of accumulation of excess electrical energy in the form of hydrogen, 3 options of the organization of work were considered. Based on the research object, the presence of boundary conditions for the ratio of the minimum and maximum differentiated tariff for the purchase of electric energy of the UES has been determined, under which it is advisable to further consider the economic indicators of the project for integrating a module for accumulating electric energy in the form of hydrogen into the scheme of a mini-CHP plant on LP.